Digital medical humanities: stage-to-screen lessons from a five year initiative - D’Alessandro, Paul; Frager, Gerri (Medical humanities, 2017)
Translation of curriculum materials to digital formats has become increasingly common. Medical humanities, typically reliant on human interaction to generate emotional impact, represents an interesting means to study engagement with digitised content. While technology-enhanced learning may provide opportunities to integrate humanities into curricula, redesigning sessions for digital use can be resource intensive and 'requires consideration of the affordances' of different media. As previously reported in BMJ Medical Humanities, guidance for this process-beyond simply, 'digitising existing content'-remains limited. We present a five year educational case study that outlines our successes and struggles with digitising a medical humanities session for undergraduate medical education.